A comprehensive active learning method for multiclass imbalanced data streams with concept drift - Liu, Weike; Zhang, Hang; Ding, Zhaoyun; Liu, Qingbao; Zhu, Cheng (Knowledge-based systems, 2021)
A challenge to many real-world applications is multiclass imbalance with concept drift. In this paper, we propose a comprehensive active learning method for multiclass imbalanced streaming data with concept drift (CALMID). First, we design a comprehensive online active learning framework that includes an ensemble classifier, a drift detector, a label sliding window, sample sliding windows and an initialization training sample sequence. Next, a variable threshold uncertainty strategy based on an asymmetric margin threshold matrix is designed to comprehensively address the problem that a given class can simultaneously be a majority to a given subset of classes while also being a minority to others. Last but not least, we design a novel sample weight formula that comprehensively considers the class imbalance ratio of the sample’s category and the prediction difficulty. On 10 multiclass synthetic streams with different imbalance ratios and concept drifts, and on 5 real-world imbalanced streams with 7 to 55 classes and unknown drifts, the experimental results demonstrate that the proposed CALMID is more effective and efficient than several state-of-the-art learning algorithms.